Effect of adsorbent and acidulants on enzymatic browning of sugarcane juice - Hithamani, Gavirangappa (J Food Sci Technol, 2018)
Enzymatic browning is a major factor affecting the quality of sugarcane juice, mainly due to the activities of polyphenol oxidase (PPO) and peroxidase (POD). Effect of bentonite (0–1%, w/v) on the activities of these enzymes, when employed alone and also in combination with acidulants, was determined. Bentonite alone could reduce the activities of PPO and POD enzymes to 160 and 24.2 u/mL, respectively. The PPO and POD activity was completely inhibited below pH 4.1 when ascorbic acid was used alone or in combination with bentonite. However, PPO and POD activity was inhibited to 60 and 51 u/mL, respectively, at pH 3.7 when citric acid was used individually and to 112 and 15.36 u/mL, respectively, when employed along with bentonite. In addition, color changes at 4 and 10 °C were measured during the storage of sugarcane juice. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13197-018-3350-4) contains supplementary material, which is available to authorized users.